Risk Factors for Acute Respiratory Infection in Toddlers : A Case Control Study - Elpira Asmin; Mira Juanita; Vebiyanti Tentua (Halu Oleo University, 2022)
Background: Acute Respiratory Infection (ARI) is a disease that attacks the upper and lower respiratory tract caused by bacteria and viruses. ARI is one of the causes of high morbidity and mortality in under-fives. Purpose(s): This study aims to determine the relationship between toddler age, immunization status, smoking habits of family members, mother's knowledge, and residential density to the incidence of ARI in the working area of the Namlea Health Center in 2021 Methods: This study is a research study quantitative analysis using a case control research design. The sample in the case group was taken using the simple random sampling method and the control group was taken using the accidental sampling method. Results: the age of toddlers who were 36 months (55.2%), incomplete immunization status (46.9%), smoking habits of family members (68.8%), low maternal knowledge (30.2%), and density of bedroom occupancy (60.4%). The results of the chi-square test showed that the p-values for each variable were age (p = 0.035), immunization status (p = 0.017), room occupancy density (p = 0.022), mother's knowledge (p = 0.046), and smoking habits. family members (p = 0.036). Conclusion: There is a significant relationship between age, immunization status, room occupancy density, mother's knowledge, and smoking habits of family members with the incidence of ARI in children under five in the working area of the Namlea Health Center in 2021.